GENETIC ANALYSIS OF COMBINING ABILITY AND GENE ACTION FOR DOUBLE CROSS HYBRIDS IN MAIZE USING RAWLINGS AND COCKERHAM METHOD - & et al., Al-Amery (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Six inbred lines (Syn-1, MGW-3, S-165, Syn-22, Zm-9, M-17) of maize (Zea mays L.) were used in this study using half diallel cross and developed 15 F1 single crosses . The single crosses were crossed a ccording to Rawllings and Cookerham method and developed 45 double crosses . Seeds of double crosses were cultivated to study combining ability and gene action of the parent. The results showed highly sinificant differences for mean square of double crosses and for the some traits . The double crosses (Syn-1* ZM-9)(MGW-3 * M-17) , (Syn-1 * ZM-9)(S-165 * Syn-22) , (MGW-3 *M17)(S-165 *Syn-22) , (Syn-1 *S-165)(MGW-3*Syn-22) (Syn-1 *S-165)(ZM-9* M17) and (MGW-3 * Syn-22)(ZM-9 *M-17) revealed highest specific combining ability effects for leaf area , number grains.ear-1and grain yield gms.plant-1 . All characters were under the epistatic gene effect with type of gene action (Dominance * Dominance) except leaf area was under the type of gene action (Additive*Dominance).